Protagonismo of the Nurse in interventions in cardiorespiratory arrest situations (Research, Society and Development, 2025)
This study aimed to analyze the role of nurses in the face of cardiopulmonary arrest (CPA), highlighting their importance in early identification, conducting cardiopulmonary resuscitation (CPR) maneuvers, and organization of the nursing team during emergency situations. This is a systematic review of the literature, with a qualitative approach, carried out through research in the Virtual Health Library (VHL), using the descriptors: “Cardiopulmonary arrest”, “Urgency and emergency” and “Nursing care”. Specific inclusion and exclusion criteria were applied, with a time frame from 2020 to 2025, resulting in the final selection of nine relevant articles. The results demonstrated that nurses play a fundamental role in all phases of CPA care, from recognizing altered vital signs to leading the team during CPR maneuvers. The literature also highlights the importance of organizing the environment, preparing the emergency cart, administering medications, providing ventilatory support, and effectively communicating with family members. Continuous education and regular training are highlighted as essential strategies for technical qualification, rapid decision-making, and standardization of conduct. It is concluded that nurses not only perform technical functions, but also act as central figures in the management of care in critical contexts. Their strategic role contributes significantly to reducing mortality, improving clinical outcomes, and promoting patient safety.